(3LZQGajI GdCMjGAs (3GdCSGSjGJ GdcGedI (B/s - (3GdeXaQ, eMSf YHO GdUGMHs ((3YeGf, GdCQOf (B:s (3OGQ UaGA ddWHGYI ddfTQ hGdJhRjY,s, 2004)
(3MjGI, LZQGajI, fTCI, JWhQ cGFfGJ, hfXe HjFjI(B.s
(3HHdjhLQGajI (B: (3U(B. 475-485. s
1.
Keywords: (3GdLZQGajG GdMjhjIs; (3Yde GdCMjGAs; (3Yde GdMaQjGJs